Regional Logistics of Procurement of the Ferrous Scrap by the Iron-and-Steel Companies of the Russian Federation - Ivanova, Tatiana Aleksandrovna; Trofimova, Violetta Shamilyevna; Kalitaev, Alexandr Nikolaevich; Stepanov, Dmitry Gennadyevich (Economy of Regions, 2017)
The article discusses the relevant problem of iron-and-steel companies saving on purchasing the scrap metal. The analysis of the current state of the ferrous scrap market in the Russian Federation, trends of its development, led the authors to an opportunity to reduce the cost for purchasing scrap trough the optimal distribution of the regions between Russian iron-and-steel companies where they purchase ferrous scrap. The optimization of the regional structure of the scrap procurement taking into account the regional volumes of its generation and consumption results from using the linear programming methods applying three variants of the problem statement: minimizing the total cost of the scrap delivery to the factory, minimizing the total cost of the scrap at the “export parity” price with delivery, minimizing the total cost of the scrap at the actual prices with delivery. The authors have developed software for performing the calculations. The source are the database of the JSC Russian Railways, which provides information about the transportation of the ferrous scrap between stations of the Russian Federation by railroad; railway rates guide between railway stations of the Russian Federation; statistical data on the prices for scrap metal of the type 3A in “export windows”; actual purchasing prices for the scrap of the 3A type for the range of separate companies of the Russian Federation for several years. As a result, the authors have obtained the optimal regional structure of scrap purchasing for customers in the Russian Federation. We have formulated the recommendations for individual companies regarding the optimal routes of the procurement with scrap. The study has confirmed the possibility to decrease expanses for purchasing the scrap metal for all iron-and-steel factories of the Russian Federation through the optimization of the regional structure of procurement. It is also has allowed to estimate the possibility to cut expenses by using the optimal strategies allowing to choose the region of procurement.